2011
DOI: 10.1227/neu.0b013e3181ff692b
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation With the Omega-3 Fatty Acid Docosahexaenoic Acid in Traumatic Brain Injury

Abstract: Dietary supplementation with DHA increases serum levels and, if given prior to traumatic brain injury, reduces the injury response, as measured by axonal injury counts, markers for cellular injury and apoptosis, and memory assessment by water maze testing. This uniform response was seen for the highest dosage group, 40 mg/kg given over 30 days prior to injury, but when measured by stereological counting methodology there was a positive response to anatomical injury across low to high doses of DHA. The potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 46 publications
3
93
2
Order By: Relevance
“…10 Alternately, dietary supplementation with DHA prior to traumatic brain injury reduces injury response, as measured by axonal injury counts, apoptosis, and memory assessment by water maze testing. 12 In addition, in the current study, chronic cerebral hypoperfusion injured rats were found to be significantly poor in retaining avoidance memories (Figure 4) on the passive avoidance task, compared to the same in NC rats. BCCAO rats have either failed to learn or failed to retrieve memory of the previous unpleasant experience of foot shock delivered in the dark compartment and demonstrates poor retention memory as evidenced by short latency to enter the dark compartment compared to the same in NC.…”
supporting
confidence: 45%
See 1 more Smart Citation
“…10 Alternately, dietary supplementation with DHA prior to traumatic brain injury reduces injury response, as measured by axonal injury counts, apoptosis, and memory assessment by water maze testing. 12 In addition, in the current study, chronic cerebral hypoperfusion injured rats were found to be significantly poor in retaining avoidance memories (Figure 4) on the passive avoidance task, compared to the same in NC rats. BCCAO rats have either failed to learn or failed to retrieve memory of the previous unpleasant experience of foot shock delivered in the dark compartment and demonstrates poor retention memory as evidenced by short latency to enter the dark compartment compared to the same in NC.…”
supporting
confidence: 45%
“…group. 12 Based on these studies, we hypothesize that combined Cho-DHA prior to chronic cerebral hypoperfusion injury will preserve cognitive functional integrity.…”
Section: Introductionmentioning
confidence: 99%
“…By modifying the Marmarou weight-drop model of concussion, we have been able to diminish impact forces to effect no obvious reaction or behavior change, and thus simulating less than a concussive injury. 2,[51][52][53] Using staining for amyloid precursor protein, we have shown that these subconcussive impacts reliably produce tearing of axons and the formation of axonal retraction bulbs in the brainstem-level descending motor pathways. In reducing the fall height of a 450-g mass from 2 to 1 m, we found no alteration of consciousness or responsiveness but significant numbers of amyloid precursor protein-positive axons compared with the number in controls (JD Mills, JE Bailes, unpublished data, 2010).…”
Section: Laboratory Evidence Of Subconcussive Effectsmentioning
confidence: 99%
“…This is consistent with previous work showing that n-3 PUFAs prevent neuronal death induced by multiple stimuli, including serum deprivation, 19 amyloid-Ī² oligomers, [20][21][22] and traumatic brain damage. 23,24 However, there is some controversy in that treatment with DHA or EPA has also been reported to increase neuronal death in response to prion protein. 25,26 Thus, it is possible that the effects of n-3 PUFAs on neuronal survival depend on the nature of the stimulus or insult.…”
Section: Strokementioning
confidence: 99%